2013
DOI: 10.7314/apjcp.2013.14.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Communication Competencies of Oncology Nurses in Malaysia

Abstract: This paper reports on part of a large study to identify competencies of oncology nurses in Malaysia. It focuses on oncology nurses' communications-related competency. As an important cancer care team member, oncology nurses need to communicate effectively with cancer patients. Literature shows that poor communication can make patients feel anxious, uncertain and generally not satisfied with their nurses' care. This paper deliberates on the importance of effective communication by oncology nurses in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
13
0
3
Order By: Relevance
“…Therefore, most decisions are made without even consulting nurses, who are the main physical caregivers for patients. Clear communication between patients and nurses and nurses with medication prescribers often play an important role in achieving effective pain management and to enhance patients' rapport (Park et al, 2012;Maskor et al, 2013). Therefore, future research may need to reexamine our nurses' attitudes and communication with other medical professionals.…”
Section: Doimentioning
confidence: 99%
“…Therefore, most decisions are made without even consulting nurses, who are the main physical caregivers for patients. Clear communication between patients and nurses and nurses with medication prescribers often play an important role in achieving effective pain management and to enhance patients' rapport (Park et al, 2012;Maskor et al, 2013). Therefore, future research may need to reexamine our nurses' attitudes and communication with other medical professionals.…”
Section: Doimentioning
confidence: 99%
“…An effective communicator is a person that can provide accurate information during a certain situation and later is capable to build trust and relationship (Maskor, Krauss, Muhamad & Nik Mahmood, 2013). Providing relevant business information is the action that would help the informants communicate eloquently and develop a good rapport.…”
Section: Providing Relevant Business Informationmentioning
confidence: 99%
“…This study has identified that the Initial Meeting Phase is the crucial stage for the informants in demonstrating their ability to communicate competently with others. Once they gain trust from these new relationships (Maskor et al, 2013), they start to level up their conversations to the next phase, the Meeting Phase. At this stage, they just focused on their own task which is to achieve their business meeting's goal.…”
Section: Remain Calmmentioning
confidence: 99%
“…Namun begitu, kajian tentang kanser serviks dalam bidang komunikasi masih sedikit. Walaupun terdapat kajian yang membincangkan komunikasi kesihatan namun tumpuannya adalah pada proses komunikasi di antara pakar perubatan dengan pesakit (Khan, Hassali, Hassali, & Al-Haddad, 2011;Nor Aida Maskor et al, 2013;Norazah Mohd Suki & Norbayah Mohd Suki, 2011;Tan et al, 2012). Oleh hal yang demikian, kajian ini bertujuan untuk mengenal pasti kesan pengantaraan penggunaan komunikasi interpersonal untuk mendapatkan maklumat tentang kanser serviks terhadap perkaitan antara penggunaan media massa dengan motivasi untuk menjalani ujian calitan.…”
Section: Pengenalanunclassified